Number of Iteration Analysis for Complex FSS Shape Using GA for Efficient ESG - Nornikman Hassan; Zahriladha Zakaria; Badrul Hisham Ahmad; Naim Che Pee; Siti Nadzirah Salleh; Mohamad Zoinol Abidin Abd Aziz; Mohd Fareq Abdul Malek; Mohd Khairy Ismail (Institute of Advanced Engineering and Science, 2018)
ESG stand for Energy-Saving Glass is a special shielded glass with a metallic oxide layer to abuse undesirable of infrared and ultraviolet radiation into construction assemblies like our home. Firstly, different number of the iteration is the main thing to study a performance of the frequency selective surface shape using genetic algorithm (GA) for efficient energy saving glass (ESG). Three different values for the number of iterations were taken that is 1500, 2000 1nd 5000. Before that, the response of this complex FSS shape on incident electromagnetic wave with different symmetry shape are investigating. Three of them are no symmetrical shape, ¼ symmetrical shape, and 1/8 symmetrical shape. The 1500 number simulation considered about 89.000 per second, compared with 2000 iteration and 5000 iterations had consumed 105.09 per second and 196.00 per second, respectively. For 1/8 symmetry complex FSS shape, it demonstrations the improved performance of transmission loss at 1.2 GHz with - 40 dB. A 2 dB of transmission loss is achieved at WLAN application of 2.45 GHz with 0°, 30°, and 45° incidence angle shows.